The Effect Ratio of Jackfruit Seed Extract With Red Dragon Fruit Extract and Stabilizer Ratio on the Quality of Dragon Fruit Yoghurt - Dewi Fahrunisa Manurung; Herla Rusmarilin; Ridwansyah Ridwansyah (Universitas Sumatera Utara, 2014)
This study was conducted to determine the effect of jackfruit seed extract comparison with the red dragon fruit juice and types of stabilizers suitable to produce the quality and organoleptic yoghurt mixture of jackfruit seed extract and red dragon fruit juice. This research was conducted at the Laboratory of Food Technology, Faculty of Agriculture, University of Sumatera Utara, Medan, using completely randomized design with two factors, i.e ratio of jackfruit seed extract and red dragon fruit juice (D): (75%: 25%, 50%: 50%, 25% : 75%) and ratio of carboxyl methyl cellulose (CMC) and Arabic gum (F) ( 0.2%): (3: 0, 2: 1, 1: 2; 0: 3). The parameters analyzed were total solids content, protein content, fat content, vitamin C content, total lactic acid, total dissolved solids, total microbes, score of color, taste, texture, and organoleptic tests of color, aroma, flavor , and texture. The results showed that the ratio of jackfruit seed extract and red dragon fruit juice had highly significant effect on total solids, protein content, fat content, vitamin C content, total lactic acid, total dissolved solids, total microbe, score of color, flavor, and hedonic value of the color, aroma, flavor, and texture. Ratio of carboxy methyl cellulose (CMC) and Arabic gum had highly significant effect on levels of protein, fat, vitamin C, total lactic acid, total microbes, score of color, taste, texture. The interaction between the two factors had highly significant effect on fat content, protein content, and total microbial and did not differ significantly to the total solids, vitamin C, total lactic acid, total dissolved solids, score of color, taste, and texture, the hedonic value of the color, aroma, flavor, and texture. Ratio of jackfruit seed extract juice of the red dragon juice (25%: 75%) and carboxyl methyl cellulose ratio (CMC) and arabic gum of (0 : 3) produce the best quality fruit yogurt and more acceptable. Keywords : Arabic Gum, Carboxy methyl cellulose, Jackfruit seeds, Red dragon fruit, Yoghurt.